The tempest - Shakespeare, William, 1564-1616.; Crowther, John (John C.) (New York : SparkNotes, 2003)
Presents the complete text of William Shakespeare's "The Tempest," with a line-by-line translation of the play in simple language, a list of characters, and a commentary.
"The play plus a translation anyone can understand"--Cover.
Young Adult
Young Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Fathers and daughters -- Drama; Islands -- Drama; Magicians -- Drama; Political refugees -- Drama; Shipwreck victims -- Drama; Spirits -- Drama; Father-daughter relationship -- Drama; Islands -- Drama; Magicians -- Drama; Political refugees -- Drama; Shipwrecks -- Drama; Spirits -- Drama; Tragicomedy; Tragicomedy